2011
DOI: 10.1213/ane.0b013e3182025a70
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effect of Propofol and Remifentanil Combinations for Sedation-Analgesia in Endoscopic Procedures Using an Adaptive Neuro Fuzzy Inference System (ANFIS)

Abstract: A model relating C(e)pro and C(e)remi to AAI/2, BIS, and IoC has been developed and prospectively validated. Based on these models, the (C(e)pro, C(e)remi) concentration pairs that provide an RSS score of 4 range from (1.8 μg·mL(-1), 1.5 ng·mL(-1)) to (2.7 μg·mL(-1), 0 ng·mL(-1)). These concentrations are associated with AAI/2 values of 25 to 30, BIS of 71 to 75, and IoC of 72 to 76. The presence of noxious stimulation increases the requirements of C(e)pro and C(e)remi to achieve the same degree of sedative ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 24 publications
2
26
0
1
Order By: Relevance
“…Both the initial target concentrations and the magnitude of the target changes were based on previous work from our group. 1 …”
Section: Drug Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the initial target concentrations and the magnitude of the target changes were based on previous work from our group. 1 …”
Section: Drug Administrationmentioning
confidence: 99%
“…The initial target intervals of propofol and remifentanil concentrations to be used in a TCI system for sedation-analgesia in ultrasonographic endoscopic (USE) procedures of the gastrointestinal tract were previously defined. 1 The hierarchical model of the interaction of hypnotic and analgesic effects proposes that opioids could act at different levels in the nervous system attenuating how the noxious stimuli get to the cortex. 2,3 Depending on the intensity reaching cortical levels, an arousal response could be detected on measures of hypnotic effect, as the bispectral index (BIS), observing an increase in BIS value.…”
mentioning
confidence: 99%
“…To adjust the algorithm input parameters, an analysis was previously conducted on 106 BIS signals collected from a patients under similar anesthetic procedures to the ones described in section 2.2 [7,6]. From that, the parameters λ and δ were set equal to 20 and 10, respectively.…”
Section: Algorithm Input Parametersmentioning
confidence: 99%
“…Previous work from our group showed that the qNOX, a parameter extracted from the raw EEG using an adaptive neuro-fuzzy inference system (ANFIS), could predict the likelihood of movement response to different anesthetic and surgical stimuli [23]. ANFIS is a data driven modelling approach based on the principles of Fuzzy Logic.…”
Section: Introductionmentioning
confidence: 99%